Individual and neighborhood characteristics as predictors of depression symptom response. (4th March 2019) - Panaite, Vanessa; Bowersox, Nicholas W.; Zivin, Kara; Ganoczy, Dara; Kim, Hyungjin Myra; Pfeiffer, Paul N.
Abstract : Objective: Assess whether neighborhood characteristics predict patient‐reported outcomes for depression. Data Sources: VA electronic medical record data and U.S. census data. Study Design: Retrospective longitudinal cohort. Data Extraction Methods: Neighborhood and individual characteristics of patients (N = 4, 269) with a unipolar depressive disorder diagnosis and an initial Patient Health Questionnaire (PHQ‐9) score ≥10 were used to predict 50 percent improvement in 4‐8‐month PHQ‐9 scores. Principal Findings: The proportion of a patient's neighborhood living in poverty (OR = 0.98; 95% CI: 0.97‐.1.00; P = 0.03) was associated with lower likelihood of depression symptom improvement in addition to whether the patient was black (OR = 0.76; 95% CI:0.61‐0.96; P = 0.02) had PTSD (OR = 0.59; 95% CI:0.50‐0.69; P < 0.001) or had any service‐connected disability (OR = 0.73; 95% CI:0.61‐0.87; P < 0.001). Conclusions: Neighborhood poverty should be considered along with patient characteristics when determining likelihood of depression improvement.